A review on recent developments in N-methylation using CO2. Issue 54 (December 2021) - Lin, Shanshan; Liu, Jianguo; Ma, Longlong
Highlights: CO2 is an abundant and green sustainable C1 building blocks for high value chemicals. N -methylation using CO2 for amines synthesis is a green, environmental and cost-effective method. Heterogeneous and homogeneous noble and non-noble metal catalysts have shown wide application in N -methylation with CO2 . New metal-free catalysts like B(C6 F5 )3, MOF, and N-heterocyclic carbenes have shown great potential applications. Abstract: Owing to the increasing emissions of carbon dioxide (CO2 ) in recent years, people's interest in the use of CO2, especially the synthesis of value-added chemicals with CO2 as a C1 blocking, has also increased year by year. In particular, the N -methylation reaction of CO2 to synthesize amines has attracted widespread attention. As an important raw material for chemical synthesis, methylation products have a wide range of uses in industry and even in nature. Using CO2 to replace traditional methylation reagents is not only green and environmentally friendly but also reduces costs. To overcome the thermodynamic and kinetic stability of CO2 and improve the selectivity and conversion rate of the N -methylation reaction, researchers are committed to the development of high-efficiency catalysts such as noble metal-supported or homogeneous catalysts, non-noble metals such as Cu, Ni, Zn, and some new metal-free catalysts. This paper summarizes and reviews the research progress and applications in the high-efficiency catalyst systems and catalytic reaction process conditions of CO2 and H2 (or organosilane) and amines to form N -methylamine and N, N -dimethylamine compounds in recent years. It is expected to provide a reference for the development of new processes for the catalytic conversion of CO2 into high value-added chemicals.